Experimental and theoretical investigation of parametric sensitivity and dynamics of a continuous stirred tank reactor for acid catalyzed hydrolysis of acetic anhydride - Jayakumar, N.S.; Agrawal, A.; Hashim, M.A.; Sahu, J.N. (Elsevier, 2011)
The continuous stirred tank reactor is a dynamic system exhibiting nonlinear behavior such as multiplicity and oscillations and, in certain range of operating conditions, may exhibit a parametric sensitivity where small changes in one or more of the input parameters lead to large changes in the output variable. In the present work, hydrolysis of acetic anhydride reaction system was used to demonstrate the existence of parametric sensitivity with respect to the input parameter, the cooling water flow rate. The applications of parametric sensitivity analysis were used for detection of parametric sensitivity in a continuous stirred tank reactor using catalyses hydrolysis of acetic anhydride reaction system. Also, theoretical investigation revealed that the effect of wall capacitance has definite influence on the dynamics of continuous stirred tank reactor. The continuous stirred tank reactor showed parametric sensitivity both in the regions of uniqueness and multiplicity, and a mathematical model was developed for the reactor. The numerically simulated results are in satisfactory agreement with the experimental data.